Development of an Android-Based Camera Rental System Application for Kedai Kamera Depok Using Android Studio Dolphin 2021.3.1 with the Rapid Application Development Method - Fitrah, Sephvinna Yanurisa; Koryanto, Lucky; Faizah, NM (Journal Mobile Technologies (JMS), 2024)
In the contemporary digital landscape, the rental of goods has become a vital service model, driven by demands for accessibility. Kedai Kamera Depok, located in Depok City, Indonesia, is a key provider of camera rental services. However, customers often face significant challenges in accessing reliable information about item availability and specifications. As the business grows, it struggles to market its offerings effectively. This study employs the Rapid Application Development (RAD) methodology, encompassing phases like Requirements Gathering, Design Workshop, and Implementation. Data was collected via structured questionnaires from Kedai Kamera Depok’s customers, ensuring user needs are integrated. The research aims to develop an Android-based reservation system for camera rentals, enabling seamless booking through mobile devices. Designed to enhance customer satisfaction and operational efficiency, this system seeks to address informational gaps and improve service delivery. The findings are expected to contribute to digital transformation in service-oriented businesses, offering a replicable model for similar enterprises facing comparable challenges in localized.